ANALISIS YURIDIS TERKAIT DENGAN PEMBERIAN SANKSI PIDANA PELAKU PEMBUNUHAN BERENCANA TERHADAP ANAK - Joana Petra Naomi; Erdianto Erdianto; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Intentional and premeditated murder (moord) is regulated in Article 340 of theCriminal Code. Where the crimes of premeditated murder committed by parents againsttheir children are very concerning. Sanctions for perpetrators of premeditated murderof children are still relatively light, which takes the lives of children. This study aims todetermine the application of law based on judge's decisions in several cases ofpremeditated murder of children and to find out the ideal sanction imposed by judges onpremeditated murder of children in the future. This study also uses the Theory of Justiceand the Theory of Punishment as an analytical knife in analyzing criminal sanctionsagainst the perpetrators of premeditated murder against. The type of legal researchused in this research is a literature study or document study and this research isreferred to as normative research (legal research) using secondary data.The data analysis used is qualitative analysis as a basis for research proceduresthat produce descriptive data, namely collecting all data obtained from primary legalmaterials and secondary legal materials. The results and discussion show that theapplication of criminal sanctions against perpetrators of premeditated murder ofchildren is still relatively light so that it does not reflect the justice and expediency ofthe law.Therefore, there is a need for criminal renewal in the application of criminalsanctions against perpetrators of premeditated murder of children as an ideal sanctionwith a minimum of 20 years. The conclusions and suggestions in this study are that theapplication of sanctions to perpetrators of premeditated murder of children must beadjusted to what has been done in order to create a sense of justice and the benefit ofthe law for both the victim's family and the surrounding environment.Keywords: Criminal Offense, Child Murder, Sanction Application, Perpetrator